A new subspecies of Ropalopus (Ropalopus) ungaricus (Herbst, 1784) from southern Spain, Ropalopus (Ropalopus) ungaricus occidentalis ssp. nov. (Coleoptera: Cerambycidae) - López, Marcos A.; Baena, Manuel (Zootaxa, 2022)
Ropalopus (Ropalopus) ungaricus occidentalis ssp. nov. is described, illustrated and compared with the other subspecies of Ropalopus (Ropalopus) ungaricus (Herbst, 1784). The new subspecies is close to Ropalopus (Ropalopus) ungaricus ossae Karpiński, Szczepański & Kruszelnicki, 2020. Data about the distribution, habitat and bionomy of the new subspecies and a keys to separation of the subspecies of Ropalopus (Ropalopus) ungaricus are given.